2012
DOI: 10.7705/biomedica.v32i4.799
|View full text |Cite
|
Sign up to set email alerts
|

Estudio IDEA (International Day for Evaluation of Abdominal Obesity): prevalencia de obesidad abdominal y factores de riesgo asociados en atención primaria en Colombia

Abstract: Contribución de los autores:Álvaro J. Ruiz: dirigió la logística de selección de participantes, intervino en la evaluación de sujetos para el estudio, revisó y limpió la base de datos, hizo el análisis estadístico y la interpretación de resultados. Pablo J. Aschner: intervino en la evaluación de sujetos para el estudio, hizo aportes significativos al análisis estadístico y al análisis de resultados. Rafael Alfonso-Cristancho: participó en la logística de planeación del estudio, en la selección de médicos parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
16

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
(22 reference statements)
1
9
0
16
Order By: Relevance
“…There is a greater risk of accumulation of intra-abdominal adipose tissue mainly in middle-aged women (40 -59 years). In this study the highest percentage was identified in this age group (57.3%) and it is known that the distribution of fat in the abdominal region is recognized as a risk factor for metabolic disorders and cardiovascular diseases [18]. Apart from this variable, the analysis of other socioeconomic variables, such as ethnicity, schooling and income, as well as its association with anthropometric, clinical and nutritional parameters in detriment of central obesity is of utmost importance, considering the lack of evidence published on such aspects.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…There is a greater risk of accumulation of intra-abdominal adipose tissue mainly in middle-aged women (40 -59 years). In this study the highest percentage was identified in this age group (57.3%) and it is known that the distribution of fat in the abdominal region is recognized as a risk factor for metabolic disorders and cardiovascular diseases [18]. Apart from this variable, the analysis of other socioeconomic variables, such as ethnicity, schooling and income, as well as its association with anthropometric, clinical and nutritional parameters in detriment of central obesity is of utmost importance, considering the lack of evidence published on such aspects.…”
Section: Discussionmentioning
confidence: 61%
“…Low schooling level is a variable that most contributes in literature to associated central obesity, justified by differences in health behaviors, including the consumption of food with better nutritional content, a clearer perception of risks related to the choices of life styles and improved self-control [18].…”
Section: Discussionmentioning
confidence: 99%
“…Se observa que en las mujeres es más frecuente el aumento del perímetro abdominal y la obesidad, resultados cercanos a los de Patiño 25 , donde el 59,1% de las personas de sexo femenino presentaron un perímetro abdominal aumentado y el 22,3% obesidad. De acuerdo a Ruiz 26 la obesidad abdominal en Colombia es mayor en las mujeres, reportando un promedio de 86,2±13,1cm. En Soledad, Atlántico, Nava-±13,1cm.…”
Section: Resultsunclassified
“…21 Además, el imc es uno de los indicadores antropométricos que evidencian mayor correlación con el perfil lipídico en ambos sexos, por lo que es muy útil para considerar los riesgos de enfermedades cardiovasculares. 22 El riesgo de presentar un episodio cardiovascular en diez años entre el personal administrativo de la ujmd de 40 años de edad o más (56.1% de población total), obtenido con la calculadora de riesgo para dispositivos móviles creada por la ops, es bajo para el 96.5% (139/144); sin embargo, a estas personas no debe considerárselas con «ausencia de riesgo», por lo que se sugiere un manejo centrado en procurar un mejor estilo de vida. En un nivel más arriba, el 2.7% (4/144) resultó con riesgo moderado, por lo que su perfil debe ser monitoreado cada 6-12 meses; mientras que el 0.8% (1/144) obtuvo riesgo alto de sufrir un episodio cardiovascular (mortal o no), y debe ser monitoreado cada 3-6…”
Section: Figura 2 Riesgo Cardiovascular Según El Imcunclassified